1992
DOI: 10.1007/bf00158578
|View full text |Cite
|
Sign up to set email alerts
|

In vitro sensitivity of Penicillium marneffei and Pythium insidiosum to various antifungal agents

Abstract: Ten isolates of Penicillium marneffei and eight of Pythium insidiosum were tested for their in vitro sensitivity to amphotericin B, hamycin (a polyene heptaene), two water-soluble analogs of amphotericin B and hamycin, namely, JAI-Amb, and JAI-hamycin,5-fluorocytosine, fluconazole, itraconazole,ketoconazole and miconazole. Itraconazole manifested the strongest activity against all of the 10 isolates of P. marneffei and would be the drug of choice in the treatment of penicilliosis due to P. marneffei. The polye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
22
0
2

Year Published

1993
1993
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 16 publications
(8 reference statements)
3
22
0
2
Order By: Relevance
“…Our MIC data for itraconazole are similar to those reported by others (1,7,10), which collectively show that this fungus is extremely sensitive to this drug. Owing to the correlation of in vitro susceptibility testing data and clinical response for itraconazole, we believe that the low MICs (geometric mean titers: itraconazole, 0.04 g/ml; terbinafine, 0.09 g/ml) indicate a similar potential clinical correlation for terbinafine.…”
supporting
confidence: 90%
“…Our MIC data for itraconazole are similar to those reported by others (1,7,10), which collectively show that this fungus is extremely sensitive to this drug. Owing to the correlation of in vitro susceptibility testing data and clinical response for itraconazole, we believe that the low MICs (geometric mean titers: itraconazole, 0.04 g/ml; terbinafine, 0.09 g/ml) indicate a similar potential clinical correlation for terbinafine.…”
supporting
confidence: 90%
“…Our MIC data for 5FC and ITC are similar to those reported by Sekhon et al (13). An in vitro study by McGinnis et al (10) demonstrated that 30 strains of P. marneffei were susceptible to ITC (MICs, 0.03 to 0.5 g/ml).…”
supporting
confidence: 89%
“…In humans, the infection occurs as ophthalmic, subcutaneous, and systemic forms, which are frequently associated with ␣-and ␤-thalassemia (5, 7). Pythiosis therapy, which is based on amphotericin B or azoles, has been ineffective or controversial, and the associated prognosis for human and equine pythiosis is poor (5,7,8,9,12). Therefore, surgical procedures, including amputation, are often effective, but disease reoccurrence rates are unfortunately high (7).…”
mentioning
confidence: 99%